Anxiety and sleep disorders: possibilities of combined phytotherapy - Чабан, Олег; Сінькевич, Інна (Psychosomatic Medicine and General Practice, 2023)
According to the WHO, the number of people suffering from anxiety disorders, sleep disorders, and depression is increasing every year, especially in low-income countries, where life expectancy is increasing dramatically, and with it the incidence of mental disorders [1, 2]. Anxiety disorders are the most common group of mental illnesses together with sleep disorders and astheno-neurotic syndrome [3]. Anxiety accompanies the course of many mental and somatic diseases [4]. It usually appears early in life, causes cumulative damage, and can contribute to depression, substance abuse, and other adverse outcomes [5]. Sleep disturbances and anxiety are frequent competing or synergistic symptoms. The onset and development of these conditions are often interrelated. In addition, these conditions often correlate with the appearance and course of other disorders - such as depression, dementia, and obsessive-compulsive disorder. Long-term, uncorrected disturbances of circadian rhythms lead to clinically significant distress and cause mental, physical, social, professional, educational, or other functional impairments [6].